ANALISIS YURIDIS TERHADAP TANGGUNG JAWAB DIREKSI(STUDI KASUS PT. X DI JAKARTA): Juridical Analysis Of The Responsibilities Of Board Of Directors (Case Study Of Pt. X In Jakarta) - Andian Fadella Rahmadani; Heru Pringgodani Sanusi (AMICUS CURIAE, 2025)
This study examines the legal liability of a Director in a Limited Liability Company (PT) who continued to perform legal acts after the expiration of their term of office, with a case study of PT. X in Jakarta. The issue identified in this research is the legal consequences and responsibilities that arise when a Director acts on behalf of the company beyond their official term. This research employs a normative legal method with a qualitative-descriptive approach using secondary data in the form of legislation and relevant documents. Based on the results of the research and conclusion, it is found that the Director's actions are deemed invalid due to the absence of legal capacity requirements under Article 98 of Law Number 40 of 2007 concerning Limited Liability Companies and Article 1320 of the Indonesian Civil Code, as well as a breach of the principles of Good Corporate Governance and Fiduciary Duty. The lack of ratification from the company confirms the invalidity of the legal act and gives rise to the Director's personal liability for any resulting loss.